MicroRNAs in diffuse large B-cell lymphoma - NI, HUIYUN (Oncol Lett, 2016)
The aberrant expression of microRNAs (miRs) has a significant impact on the biological characteristics of lymphocytes, and is important in the pathogenesis of diffuse large B-cell lymphoma (DLBCL). It has been demonstrated, using miR profiling and detecting distinct miR signatures, that certain miRs may accurately distinguish different subtypes and prognostic classifications of DLBCL, as well as distinguish DLBCL from other more indolent lymphomas, including follicular lymphoma. miRs are excellent biomarkers for cancer diagnosis and prognosis. In DLBCL, specific miR expression profiles in the tissues of patients are associated with prognosis and clinical outcome. Over the past decade, there has been substantial investigation concerning the pathogenetic, diagnostic and prognostic roles of miRs in DLBCL. The aim of the present review is to describe the aberrant expression of miRs in DLBCL, and the functions, potential clinical use and possible therapeutic targets of miRs in this disease.